Audel Installation Requirements of the 2005 National Electrical Code - Rosenberg Paul (Audel, 2005)
The voluminous 2005 National Electrical Code (NEC)® affects many disciplines, but what you need to know is how it influences your work as an installer. Organized by the type of wiring involved, this indispensable guide extracts and explains only the information that applies to installation. It's a practical reference that highlights what's new, what's changed, and what you must do to comply.